Institutional Investors and Long-Term Investment : Evidence from Chile - Opazo, Luis; Raddatz, Claudio; Schmukler, Sergio L. (World Bank, Washington, DC, 2014)
Developing countries are trying to develop long-term financial markets and institutional investors are expected to play a key role. This paper uses unique evidence on the universe of institutional investors from the leading case of Chile to study to what extent mutual funds, pension funds, and insurance companies hold and bid for long-term instruments, and which factors affect their choices. The paper uses monthly asset-level portfolios to show that, despite the expectations, mutual and pension funds invest mostly in short-term assets relative to insurance companies. The significant difference across maturity structures is not driven by the supply side of debt or tactical behavior. Instead, it seems to be explained by manager incentives (related to short-run monitoring and the liability structure) that, combined with risk factors, tilt portfolios toward short-term instruments, even when long-term investing yields higher returns. Thus, the expansion of large institutional investors does not necessarily imply longer-term markets.